PRAGMALINGUISTIC ASPECTS OF EMOTIVENESS IN ENGLISH LANGUAGE - Amira Rakhmonova; Zarina Abduhakimova (PEDAGOGS, 2024)
Abstract: This study employs a qualitative research approach, drawing on a diverse range of linguistic theories, pragmatic frameworks, and empirical data to analyze the pragma-linguistic aspects of emotiveness in English. Through a combination of literature review, discourse analysis, and case studies, it aims to uncover the intricate layers of emotive communication in English language use.